Serosurvey of Toxoplasmosis Among Drug Users in Fars Province, Southern Iran: A Cross‐Sectional Study - Mohammad Reza Cheraghi; Mina Zarrabi; Sara Shahriarirad; Sahel Rohampour; Ghazal Shayan; Mostafa Omidian; Elham Rezaee; Jamal Sarvari; Abolfazl Gheshlaghi; Qasem Asgari; Bahador Sarkari (Health Science Reports, 2026)
ABSTRACT Background and Aims Toxoplasma gondii is a widespread zoonotic protozoan that poses significant health risks, particularly to immunocompromised individuals. Although generally asymptomatic, toxoplasmosis can lead to severe neurological complications and behavioral disorders. This infection can be transmitted through various routes, including sharing needles and/or syringes with someone who is infected. The current cross‐sectional study aimed to determine the prevalence of toxoplasmosis among drug users in Fars Province in the south of Iran. Methods Subjects of the study were 1400 drug users. Blood samples were collected from each individual from June 2023 to April 2024. T. gondii antigens were prepared from the parasite's tachyzoites and used in an ELISA system to detect anti‐ Toxoplasma antibodies. The data were analyzed to explore the possible association between Toxoplasma seropositivity and participants' demographics. Results The majority (52.7%) of the participants were aged 40–60 years, with 83.4% living in urban areas. Males constituted 92.8% and females 7.2% of the subjects. Anti‐ Toxoplasma antibodies were detected in the sera of 189 individuals, corresponding to a seroprevalence of 13.5% (95% CI, 9.5%–15.4%). Notably, 89.9% of those using injection methods for substance use were infected. Moreover, 94.2% of the infected individuals were male. Our findings revealed no association between Toxoplasma seropositivity and the demographic or method of drug use in patients with substance use disorder in Fars Province in the south of Iran. Conclusion Findings of the current study underscore the need for targeted public health interventions to address the risk of toxoplasmosis in this vulnerable population, particularly among those who use injection drugs. Further research is warranted to explore the underlying factors contributing to Toxoplasma infection in this population and to develop effective prevention strategies.